The Effect of Learning Using Script Methods and Cooperative Articulation Methods Against Student Mathematical Learning Outcomes - Herayanti, Herayanti; Wahyudin, Wahyudin (International Conference on Elementary Education, 2020)
The purpose of this study was to determine the effect of learning by using the Script and Cooperative Articulation methods on improving student mathematics learning outcomes. This research is a comparative study with a research design that is only posttest design. The population of this research is grade VII students of SMP Negeri 2 Palasah, Majalengka Regency, academic year 2017/2018. The sample in this study were 59 students who were determined using cluster random sampling techniques. Data collection techniques used: (1) learning outcomes using the Cooperative Script method (2) learning outcomes using the Cooperative articulation method (3) differences in the effect of the cooperative script method with the Cooperative articulation method